2020
DOI: 10.3390/app10186378
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Nonthermal Atmospheric Plasma-Activated Water on the Structural, Optical, and Biological Properties of Aspergillus brasiliensis Spores

Abstract: Plasma-activated water (PAW) has emerged as a platform for sterilizing fungal pathogens. In this study, we investigated the influence of PAW on black melanized spores of Aspergillus brasiliensis to explore the mechanism of fungal spore inactivation. PAW was prepared by activating deionized water with a nonthermal atmospheric pressure air plasma jet (soft plasma jet). The concentrations of H2O2 and NOx in the PAW treated by the soft plasma jet for 3 min were 50 μM and 1.8 mM, respectively, and the pH of the PAW… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 62 publications
0
9
0
Order By: Relevance
“…To evaluate the extent of species involvement in the microbial inactivation of PAW, Su et al (2018) demonstrated that • OH, • NO, and H 2 O 2 were the main species that changed morphology and destroyed and degraded the RNA and protein structure, causing virus inactivation. Moreover, Guo et al (2018) suggested that 1 O 2 was the main functional agent in PAW for bacteriophage inactivation, and Ki et al (2020) reported that the long‐lived reactive species in PAW had a good inactivation effect on melanized fungal spores. In our study, the results demonstrated that long‐lived species such as NO2, NO3 were key players in bacterial inactivation, and the presented data gave evidence that O2 was a significant contributor to antimicrobial activity of PAW.…”
Section: Resultsmentioning
confidence: 99%
“…To evaluate the extent of species involvement in the microbial inactivation of PAW, Su et al (2018) demonstrated that • OH, • NO, and H 2 O 2 were the main species that changed morphology and destroyed and degraded the RNA and protein structure, causing virus inactivation. Moreover, Guo et al (2018) suggested that 1 O 2 was the main functional agent in PAW for bacteriophage inactivation, and Ki et al (2020) reported that the long‐lived reactive species in PAW had a good inactivation effect on melanized fungal spores. In our study, the results demonstrated that long‐lived species such as NO2, NO3 were key players in bacterial inactivation, and the presented data gave evidence that O2 was a significant contributor to antimicrobial activity of PAW.…”
Section: Resultsmentioning
confidence: 99%
“…As shown in Figure 5 d, the absorption spectra of the PAW and PA-Mg-W exhibited an absorption peak at 201 nm. As the reference nitrite and nitrate solutions have absorption peaks at 209 and 201 nm, respectively [ 12 , 46 ], the observed 201-nm absorption band indicates that nitrate ions greatly outnumber nitrite ions. Next, the nitrate absorption peak intensity at 300 nm was higher in the PA-Mg-W than in the PAW, as shown in Figure 5 a,b.…”
Section: Resultsmentioning
confidence: 99%
“…That is, Ascomycota fungi are characterized by gel-like α-1,3 glucans and galactomannoproteins, whereas Basidiomycota fungi are characterized by α-1,3 glucans along with xylomannoproteins [ 54 ]. In a previous work, we demonstrated that PAW influences the spore viability and cell wall integrity of the Ascomycota fungus, Aspergillus brasiliensis , which has melanized fungal spores [ 12 ]. We wondered whether PAW would be applicable to Basidiomycota fungi.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations